2002
DOI: 10.1038/sj/onc/1205008
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of MHC class I by bovine papillomavirus E5 oncoproteins

Abstract: The papillomavirus E5 protein is localized in the endoplasmic reticulum (ER) and Golgi apparatus (GA) of the host cell. Transformed bovine ®broblasts expressing bovine papillomavirus (BPV) E5 are highly vacuolated and have a much enlarged, distorted and fragmented GA. Major histocompatibility complex class I (MHC I) is processed and transported to the cell surface through the GA. Given the cellular localization of E5 in the GA and the morphologically abnormal GA, we investigated the expression of MHC I in cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
64
0
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(70 citation statements)
references
References 41 publications
5
64
0
1
Order By: Relevance
“…Thus, the ability of E5 to perturb the pH of intracellular organelles may influence the activity of many proteins and contribute to cell transformation. An important consequence of E5 mediated impaired acidification is the down-regulation (both in vivo and in vitro) of Major Histocompatibility Complex class I (MHC-I) expression, representing one of the mechanisms by which BPV evades the host's immunoresponse [9]. Down-regulation of MHC-I takes place at multiple levels: the transcription of the gene is reduced, the MHC-I heavy chain peptide is degraded [9] and the MHC-I complex is sequestered in the GA cisternae and prevented from reaching the cell surface [81].…”
Section: E5mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the ability of E5 to perturb the pH of intracellular organelles may influence the activity of many proteins and contribute to cell transformation. An important consequence of E5 mediated impaired acidification is the down-regulation (both in vivo and in vitro) of Major Histocompatibility Complex class I (MHC-I) expression, representing one of the mechanisms by which BPV evades the host's immunoresponse [9]. Down-regulation of MHC-I takes place at multiple levels: the transcription of the gene is reduced, the MHC-I heavy chain peptide is degraded [9] and the MHC-I complex is sequestered in the GA cisternae and prevented from reaching the cell surface [81].…”
Section: E5mentioning
confidence: 99%
“…An important consequence of E5 mediated impaired acidification is the down-regulation (both in vivo and in vitro) of Major Histocompatibility Complex class I (MHC-I) expression, representing one of the mechanisms by which BPV evades the host's immunoresponse [9]. Down-regulation of MHC-I takes place at multiple levels: the transcription of the gene is reduced, the MHC-I heavy chain peptide is degraded [9] and the MHC-I complex is sequestered in the GA cisternae and prevented from reaching the cell surface [81]. The molecular mechanism by which BPV-1 E5 induces cell transformation lies in its binding to, and activation of, the cellular receptor for the platelet-derived growth factor (PDGF ) [48].…”
Section: E5mentioning
confidence: 99%
“…10,11 We have shown that one of the outcomes of BPV E5 expression in primary cells is the retention of major histocompatibility (MHC) class I complexes in the GA and the inhibition of their transport to the cell surface. 12,13 Furthermore, BPV E5 inhibits both transcription of the MHC class I heavy chain gene and affects the stability of the heavy chain protein. 12 In this study, we show that HPV-16 E5 also prevents the transport of MHC (HLA) class I complexes to the cell surface due to retention in the GA.…”
mentioning
confidence: 99%
“…E5 is a small hydrophobic protein (44 aa) that is capable of inducing in vitro cell transformation through the activation of several kinases, from growth factor receptors to cdk cyclins (Venuti & Campo, 2002). E5 interacts physically with the cellular protein 16k ductin/ subunit c, a component of the gap junction and of the V0 sector of vacuolar H + -ATPase (Conrad et al, 1993;Faccini et al, 1996;Finbow et al, 1991;Goldstein et al, 1991), causing the downregulation of gap junction communication (Ashrafi et al, 2002;Faccini et al, 1996;Oelze et al, 1995) and the lack of acidification of endosomes and Golgi apparatus (GA) (Schapiro et al, 2000;Straight et al, 1995). However, its function in vivo is still unknown.…”
mentioning
confidence: 99%
“…It has been suggested that cancer cells may escape host immune control by E5-mediated downregulation of MHC class I molecules. This downregulation seems to be related to the interaction of E5 with 16k ductin/subunit c, which may lead to improper glycosylation and processing of MHC class I molecules (Marchetti et al, 2002). Since the cows from which we collected the samples had been grazing on bracken fern-infested pasture, the immunosuppression caused by the plant could enhance the escape of the E5-expressing tumour cells from the immune system.…”
mentioning
confidence: 99%